Finite Element Analysis of Composite Laminated Timber (CLT) - Juan Enrique Martínez-Martínez; Mar Alonso-Martínez; Felipe Pedro Álvarez Rabanal; Juan José del Coz Díaz (Proceedings, 2018)
In the research for sustainable construction, cross-laminated timber (CLT) has gained popularity and become a widely used engineered timber product. However, there are few numerical studies of the structural behaviour of CLT. Among other issues, the orthotropic properties of CLT complicate finite element analysis (FEA). This paper presents a finite element model (FEM) to predict the structural behaviour of CLT beams subjected to sustained flexural loading. This numerical model includes a material model based on the orthotropic material properties of different timber species. Furthermore, the orientation and the properties of each layer are considered. Most of the previous studies simulate CLT beams as a homogeneous material. However, in this work the CLT beam is modelled as a composite material made up of five layers with different orientations and properties. Bonded contacts are used to define the interaction between layers. In addition, nonlinearities, such as large displacement, are used to simulate the behaviour of CLT beams. The model provides the load-displacement relationship and stress concentration. Tsai-Wu failure criteria is used in the simulation to predict the failure modes of the CLT beams studied.